Implementation of Analytic Network Process Algorithm in E-Lowker System - Herry Derajad Wijaya; Wawan Gunawan (Journal of Systems Engineering and Information Technology (JOSEIT), 2022)
Job vacancies information system at this time that there are still many companies that use the manual method to get the best employees and the number of job applicants who have not used the internet as a medium of information, but in this case the research aims to facilitate companies in getting the best employees, namely using the ANP Method in a web-based job information system and facilitate job applicants in utilizing internet media as a source of information that has been provided by the company. The ANP method is to find the weighted sum of the performance ratings for each alternative on all attributes, in this study the programming languages ​​used are PHP, MySQL database, CSS and Java Script. The criteria used in this study are education, experience, age and expertise. In this study shows that the Implementation of the ANP Method in the Web-Based Job Vacancy Information System is able to produce the best prospective workers for the company in accordance with the criteria